The Effect of Digital Flashcard on Students' Vocabulary Mastery at Seventh Grade of SMP Negeri 1 Kramatwatu - Rahmawati, Ratu Ayu; Dahlina, Ulinuha (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
This study explores the challenges and strategies involved in English vocabulary acquisition among seventh-grade students at SMP Negeri 1 Kramatwatu, Indonesia. Historically, English has been emphasized within the Indonesian education system, yet many students continue to struggle with vocabulary mastery, particularly due to traditional teaching methods and low motivation. The research identifies key issues such as reliance on rote memorization, lack of engaging instructional techniques, and insufficient use of media tools to aid learning. To address these challenges, the study introduces the use of digital flashcards as an innovative pedagogical tool aimed at enhancing vocabulary retention and student engagement. Digital flashcards, which combine visual imagery with spaced repetition techniques, offer an interactive and stimulating learning experience. The research highlights the potential of digital flashcards to significantly improve students' vocabulary acquisition, thereby supporting their overall English language proficiency. By integrating multimedia resources into the classroom, educators can foster a more engaging and effective learning environment that caters to the diverse needs of students. This approach not only aids in vocabulary retention but also boosts students' motivation and interest in learning English, ultimately contributing to better academic outcomes.